Tongues of serpents - Novik, Naomi (Novik, Naomi. Temeraire series., 2010)
Convicted of treason despite their heroic defense against Napoleon's invasion of England, Temeraire the dragon and his friend and rider, Capt. Will Laurence, are transported to the prison colony in Australia. They carry with them three dragon eggs intended to help establish a covert in the colony.